Modern Wound Dressings as Wound Care After Necrotomy Debridement at Right Submadible extended to Submentale region due to Necrotizing Fasciitis: A Case Report - Laksmitarani, Niken; Priyanto, Winarno; Sjamsudin, Endang (Hasanuddin University, 2021)
AbstractIntroduction: Necrotizing fasciitis is a fast-paced infection, severely damaging tissue. Surgical removal of tissue must be performed promptly, and aggressively to remove all involved soft tissue. The wound left after debridement necrotomy is wide enough to close primarily and should be treated by suitable dressings to accelerate wound healing. Objective: This case report aims to understand the concept of moist wound healing, the choice of dressing material, and the principles of optimal wound intervention for the wound healing process. Case: A 58 years old female patient presented with a complaint of swelling of the right lower jaw extended to the chin region. About a month earlier the patient complained of a lower right toothache, the patient went to the public health center, the lower right tooth was extracted but there was a residual root left behind. Then the patient still felt pain in the area of the extraction and the swelling in the lower jaw got bigger, the fragility of the superficial fascia, and the absence of pus. Then the patient was referred to the emergency room at Hasan Sadikin Hospital in Bandung. Case management: The patient was performed necrotomy debridement and tooth extraction causing the infection in local anesthesia, then the wound was treated with modern dressings. After 1 month of the procedure, the wound was closed properly. Conclusion: Modern dressings are wound care using the principle of balanced moisture (moisture balance). Choosing the right dressing material is a key concept to support the wound healing process.